(3cJGH aj GdLHQ hGdebGHdIs - (3TLGY Hf GSde Hf eMeO Hf TLGY, CHh cGed,J (B340 (3g` s
(3ChdgG (B:s
(3GdMeO ddg CYOd ef Mce hCMce ef Yde hCMb ef NTi hMeO hCaVd ef QLi s
(3BNQgG (B:s
(3aeG Hbi agh CVYGa hLeY eG ef hGMO Edi CQHY hSJjf Je GdcJGH s
(3cJHJ Hbde ajg VHWs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B157s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1407s
Keywords: (3GdQjGVjGJs